Just the Facts : Pathophysiology. - Lippincott (Just the facts., 2011)
This quick-reference handbook provides the essential ""must-have"" pathophysiology facts that nurses need in day-to-day patient care. The book covers more than 130 diseases organized by body system, with separate chapters on genetics and fluid and electrolyte disorders. Information is presented in a format that is ideal for rapid access, with bullets, graphic illustrations, and flow charts that demonstrate pathophysiologic processes. Signs and symptoms are clearly linked to pathophysiologic changes in each disorder. Each chapter begins with a brief review of pathophysiologic concepts. An appen.